2006
DOI: 10.1152/ajpgi.00471.2005
|View full text |Cite
|
Sign up to set email alerts
|

Early activation of endoplasmic reticulum stress is associated with arginine-induced acute pancreatitis

Abstract: Endoplasmic reticulum (ER) stress mechanisms have been found to play critical roles in a number of diseases states, such as diabetes mellitus and Alzheimer disease, but whether they are involved in acute pancreatitis is unknown. Here we show for the first time that all major ER stress sensing and signaling mechanisms are present in exocrine acini and are activated early in the arginine model of experimental acute pancreatitis. Pancreatitis was induced in rats by intraperitoneal injection of 4.0 g/kg body wt ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
95
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 33 publications
4
95
1
2
Order By: Relevance
“…In the case of unresolvable stress, the UPR can activate a proapoptotic program and trigger cell death, thus requiring cells to maintain tight control over the master regulators and their associated target genes. Indeed, disruption of the UPR and its corresponding response pathways has been linked to cancer progression as well as to other human diseases (4)(5)(6)(7), highlighting the need to discover new regulatory and effector UPR mechanisms that can be exploited in designing strategic biotherapeutics.…”
mentioning
confidence: 99%
“…In the case of unresolvable stress, the UPR can activate a proapoptotic program and trigger cell death, thus requiring cells to maintain tight control over the master regulators and their associated target genes. Indeed, disruption of the UPR and its corresponding response pathways has been linked to cancer progression as well as to other human diseases (4)(5)(6)(7), highlighting the need to discover new regulatory and effector UPR mechanisms that can be exploited in designing strategic biotherapeutics.…”
mentioning
confidence: 99%
“…This includes dilatation or vacuolation of the ER and loss of membrane-bound ribosomes (1,17,25,27). ER changes seem a common reaction of acini to the induction of ER stress (18,23). Key regulators of the ER stress response are altered during AP and several ER-resident chaperones are upregulated.…”
mentioning
confidence: 99%
“…16 The mechanism by which PTP1B deficiency potentiates MAPK signaling remains unknown, but can be indirect and related to increased inflammation. Last, ER stress is implicated in the pathophysiology of pancreatitis, 53,67 and attenuation of ER stress by chemical chaperones mitigates the disease in animal models. 54 Increased PERK and IRE1a activation in PTP1B knockout mice and inhibitor-treated acinar cells is consistent with previous findings of enhanced PERK and IRE1a signaling in MIN6 b-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unfolded protein response is used by cells to counter the deleterious effects of ER stress and is triggered by transmembrane sensors, such as PKR-like ER-regulated kinase (PERK), that detect unfolded proteins in the ER and convey information through their cytosolic domain. 52 More important, activation of ER stress is associated with AP 53 and treatment with ER chaperones mitigates the disease in animal models. 54 In addition, we previously demonstrated that PTP1B knockdown in MIN6 b-cells enhanced PERK and inositol requiring enzyme 1a (IRE1a) signaling.…”
Section: Pancreatic Ptp1b Deficiency Regulates Cerulein-and Arginine-mentioning
confidence: 99%